Ball type and court surface: A study to determinate the ball rebound kinematics on the padel wall - Gea García, G. M.; Consea Garre, C. M.; Courel-Ibanez, J.; Menayo Antúnez, R. (International Journal of Performance Analysis in Sport, 2021)
The existence of three walls on both court sides in padel is a unique characteristic from which particular offensive and defensive behaviours emerged. The aim of this study was to assess the differences on kinematics parameters using two types of balls - Head and Dunlop - in the two-existing kind of wall surfaces - concrete and glass - during a padel drive. Data were obtained from the bounce on of two hundred padel balls on the two different surfaces. The ball type showed a greater influence on linear space and speed parameters, whilst wall surface had a greater impact on the ball angle and acceleration. In particular, glass surface showed faster, longer and more accelerated bounces than concrete. This may provide some advantages like more time to react and higher balls will increase the odds to score directly with a smash. Therefore, playing padel on a concrete surface will result in more difficulties than glass. Moreover, Dunlop balls described faster and longer bounces than Head. This information should be taken into account for coaches when defining training aims and designing specific tasks and for researchers as a control variable with potential influence on players` performances and behaviours.